Rationale for determining the types of adaptation to predict in sport - Ровний Анатолій Степанович (Anatoliy Rovnyy); Ласточкін Віктор Миколайович (Viktor Lastochkin) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: theoretical and practical study adaptation types beginners. Materials and Methods: an analytical synthesis of scientific literature data, the determination of the concentration of lactic acid testing of motor activity. Results: based on the parameters set lactate types of adaptation: «sprinters», «stayers», «mixed type». Conclusions: the establishment of types of adaptation makes it possible to recommend a special focus budding athletes in the sport